Medical Queeries: Transgender Healthcare - Tehmina Ahmad; Han Yan; Keegan Guidolin; Paul Foster (MedEdPORTAL, 2015)
Abstract Transgender individuals, particularly those who are undergoing or have undergone sex reassignment therapies or surgeries, constitute an under-serviced population when it comes to access to healthcare. This is the result of a variety of reasons. However, physician behavior and negative experiences within the health care system are both commonly cited reasons why transgender individuals fail to seek appropriate medical attention. The goal of this resource is to inform physicians and other health care providers of some of the major issues and barriers that transgender people face when seeking medical care. It also proposes several potential solutions to these problems. “Medical Queeries: Presenting Transcare Initiatives,” is an empowering educational film that provides health care workers with an opportunity to better understand and reflect upon the needs of the transgender community. The film features a transgender individual who focuses on the approaches health care providers (particularly physicians and nurses) can consider in order to improve transcare management. After viewing this video, the audience should be able to define transgender, transcare, and develop self-awareness of how to combat transgender barriers to health care. The accompanying PowerPoint presentation serves as a discussion tool to further enhance student learning. This learning module requires only a projector and screen, and a facilitator. The session can be run in 45-60 minutes, including time allotted for discussion. The length of the presentation means that it can be done over a lunch hour or fitted into a regular meeting. Discussion is key—having someone to help facilitate conversation will make the session engaging, interesting, and informative. The video has been distributed through the Association of Faculties of Medicine of Canada, and through various transgender healthcare presentations in health care settings such as the London Health Sciences Centre. It is also found on the Canadian Healthcare Education Commons.